Barriers to Educational Access and Integration Among Rohingya Children in Bangladesh: A Qualitative Policy and Community Perspective - Ullah Chowdhury, Mohammed Salamath; Bishnoi, Rajnish (International Journal of Aquatic Research and Environmental Studies, 2026)
Bangladesh currently hosts over one million forcibly displaced Rohingya refugees in the Cox’s Bazar camps, with children comprising nearly half of the refugee population. Despite extensive humanitarian interventions, access to equitable, continuous, and quality education remains severely constrained. This study examines the multidimensional barriers that impede educational access, participation, and learning outcomes among Rohingya children in Bangladesh. A qualitative multi-stakeholder research design was adopted, integrating Interpretive Phenomenological Analysis (IPA) with policy and institutional document review. Data were collected between September and December 2023 through 42 semi-structured interviews and six focus group discussions involving Rohingya parents, Learning Center facilitators, NGO personnel, camp administrators, and community leaders across five refugee camps in Cox’s Bazar. Thematic analysis was guided by Bronfenbrenner’s Ecological Systems Theory and a rights-based educational framework to capture interactions between policy, community, and individual-level determinants. Findings reveal five interrelated barriers shaping educational exclusion: (i) the persistence of a “temporariness doctrine,” whereby the absence of formal legal recognition sustains educational uncertainty; (ii) curriculum dislocation resulting from exclusion from the national education system and limited recognition of the Myanmar curriculum; (iii) a gendered dropout cascade characterized by the progressive withdrawal of adolescent girls from schooling due to entrenched sociocultural norms; (iv) psychosocial learning obstruction linked to displacement-related trauma and chronic insecurity; and (v) donor-dependent fragility, reflecting the vulnerability of educational provision to fluctuations in international humanitarian funding. These barriers operate as a mutually reinforcing system of educational exclusion. Sustainable solutions require integrated policy responses encompassing legal recognition, gender-responsive interventions, trauma-informed educational practices, and long-term financing mechanisms. The study proposes an Integrated Educational Inclusion Roadmap (IEIR) and advocates for a rights-based, refugee-sensitive educational policy framework to advance inclusive and resilient learning opportunities for Rohingya children.
Keywords: Rohingya; refugee education; Bangladesh; Cox's Bazar; educational barriers; qualitative research; policy analysis; gender gap; psychosocial wellbeing; educational integration